2023
DOI: 10.1038/s41467-023-37105-8
|View full text |Cite
|
Sign up to set email alerts
|

The cellular and KSHV A-to-I RNA editome in primary effusion lymphoma and its role in the viral lifecycle

Abstract: Adenosine-to-inosine RNA editing is a major contributor to transcriptome diversity in animals with far-reaching biological consequences. Kaposi’s sarcoma-associated herpesvirus (KSHV) is the etiological agent of several human malignancies including primary effusion lymphoma (PEL). The extent of RNA editing within the KSHV transcriptome is unclear as is its contribution to the viral lifecycle. Here, we leverage a combination of biochemical and genomic approaches to determine the RNA editing landscape in host- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 78 publications
1
12
0
Order By: Relevance
“…For instance, certain genes (CCNI, COPA, and AZIN1) exhibit more alterations in endothelial cells compared to excitatory neurons, while TMEM63B shows less alteration in endothelial cells [ 17 , 18 ]. It has demonstrated that ADARs play crucial roles in brain development, viral defense mechanisms [ 19 22 ], and various human diseases, including cancer [ 23 30 ], autoimmune diseases [ 23 , 31 , 32 ], autoinflammatory diseases [ 24 , 33 ], atherosclerosis [ 34 , 35 ], and heart failure [ 36 ]. Recent studies have also revealed the significance of ADAR2 in tissue inflammation through its control of the IL-6 signaling pathway [ 37 ].…”
Section: Backgroundsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, certain genes (CCNI, COPA, and AZIN1) exhibit more alterations in endothelial cells compared to excitatory neurons, while TMEM63B shows less alteration in endothelial cells [ 17 , 18 ]. It has demonstrated that ADARs play crucial roles in brain development, viral defense mechanisms [ 19 22 ], and various human diseases, including cancer [ 23 30 ], autoimmune diseases [ 23 , 31 , 32 ], autoinflammatory diseases [ 24 , 33 ], atherosclerosis [ 34 , 35 ], and heart failure [ 36 ]. Recent studies have also revealed the significance of ADAR2 in tissue inflammation through its control of the IL-6 signaling pathway [ 37 ].…”
Section: Backgroundsmentioning
confidence: 99%
“…Trans-regulation implies that ADARs and APOBECs interact with host viral proteins, RNA, or immune factors, without performing deamination functions and participate in host immune response pathways [ 67 ]. In both cases, host-mediated RNA editing ultimately affects the viral life cycle, host adaptation, or to some extent the evolutionary direction of the virus [ 22 , 135 ]. RNA editing in viruses has dual effects.…”
Section: Biological Functions Of Rna Editingmentioning
confidence: 99%
“…For instance, A‐to‐I editing of both host and viral transcripts has been observed in Kaposi's sarcoma‐associated herpesvirus (KSHV)‐infected cells. 74 Additionally, this A‐to‐I editing pathway undergoes further expansion during KSHV lytic reactivation, effectively preventing recognition and detection by RIG‐I‐like receptors (RLRs) pathway. Furthermore, ADAR2 edits its own pre‐mRNA and creates an alternative splicing acceptor site, effectively leading to the suppression of its own expression.…”
Section: Cellular Functions and Regulatory Enzymes Of Non‐m ...mentioning
confidence: 99%
“…There are three members of the human ADAR family, designated ADAR1 (ADAR), ADAR2 (ADARB1), and ADAR3 (ADARB2), where ADAR1 is responsible for the majority of the A-to-I editing activity in mammalian cells [ 46 ]. Widespread A-to-I editing of both the host and viral transcripts has been observed in KSHV-infected cells, and the A-to-I editomes are further expanded during KSHV lytic reactivation [ 47 ]. The A-to-I editing of the induced dsRNAs by KSHV infection prevents them from being recognized and detected by RLRs within the cell.…”
Section: Rig-i-like Receptorsmentioning
confidence: 99%
“…Recently, it has been shown that many KSHV and EBV RNAs undergo RNA modifications including methylation, A-to-I editing and pseudouridylation, which affect RNA stability, secondary structure, and protein association as well as the recognition of RNAs by RNA sensors [ 90 , 92 , 98 , 99 , 100 , 101 , 102 ]. For example, A-to-I editing of viral and host RNA can help KSHV evade the RLR sensing pathway and facilitate viral infection [ 47 , 48 ]. While m 6 A modifications of viral and host RNAs influence KSHV and EBV infections, future work should be geared towards determining how the various m 6 A readers, writers and erasers mechanistically alter various m 6 A sites in both viral and cellular mRNAs to modulate the innate immune response and whether they exhibit functional redundancy.…”
Section: Conclusion and Perspectivementioning
confidence: 99%